Combined effect of pump excited state absorption and pair-induced quenching on the gain and noise figure in bismuth oxide-based Er3+-doped fiber amplifiers - Jung, Minwan; Chang, You Min; Jhon, Young Min; Lee, Ju Han (OPTICAL SOC AMER, 2011)
The impact that pump excited state absorption (ESA) and pair-induced quenching (PIQ) have on the gain and noise figure (NF) performance of a bismuth oxide-based erbium-doped fiber amplifier (EDFA) is investigated in both theoretical and experimental manners. The gain and the NF performance are shown to significantly degrade due to the combined effect of the pump ESA and PIQ when 980nm pumping is employed. It is shown that the use of 980nm pumping does not provide any significant NF benefit relative to 1480nm pumping in highly doped bismuth oxide-based EDFAs with non-negligible PIQ, contrary to the common wisdom regarding pump wavelength-dependent NF performance. The reason turns out to be associated with a considerable population decrease in the I-4(13/2) state, caused by the mutual stimulation effect between the pump ESA and PIQ. From this investigation the better of the two pump wavelengths is found to be 1480nm when the signal gain and NF are considered together. (C) 2011 Optical Society of America
Keywords: ERBIUM-DOPED FIBER; SIGNAL